Performances of disseminated intravascular coagulation scoring systems in septic shock patients - Helms, Julie (Ann Intensive Care, 2020)
BACKGROUND: There is no gold standard to diagnose septic shock-induced disseminated intravascular coagulation (DIC). The objective of our multicenter prospective study was to assess the performances of the different major scoring systems in terms of mortality prediction and DIC diagnosis. The JAAM-DIC 2016 score, the ISTH overt-DIC 2001 score, the associations of sepsis-induced coagulopathy (SIC) score with JAAM-DIC 2016 or ISTH overt-DIC scores were tested in patients within 12 h of their admission in ICU for septic shock (day 1) and at day 2. RESULTS: 582 patients were enrolled in the study. 182/567 (32.1%) were diagnosed with DIC according to ISTH overt-DIC score, and 193/561 (34.4%) according to JAAM-DIC score; 486/577 patients (84.2%) were diagnosed with a coagulopathy according to SIC score. A moderate concordance was observed between ISTH overt-DIC and JAAM-DIC [κ = 0.67 (0.60, 0.73), p < 0.001]. The delay of positivity of the scores for early DIC patients was not different between JAAM-DIC and ISTH overt-DIC scores. Although it was positive earlier, SIC score had worse diagnosis specificity, as 84.2% of the patients with septic shock were diagnosed with “coagulopathy”. The specificity of SIC score alone to predict mortality was very low [0.18 (0.15; 0.22)], compared to the ones of JAAM-DIC score [0.71 (0.67; 0.75)], and of ISTH overt-DIC score [0.76 (0.72; 0.80)], p < 0.001. The sensitivity of SIC score to predict mortality was 0.95 [0.89; 0.98], and the ones of JAAM-DIC score and ISTH overt-DIC score were 0.61 [0.50; 0.70] and 0.68 [0.58; 0.77], respectively. There was no benefit in sensitivity and specificity in combining SIC score to JAAM-DIC score or to ISTH overt-DIC score, compared to JAAM-DIC score or ISTH overt-DIC score alone. CONCLUSIONS: Our data suggest that the added value of SIC score alone or combined with other scores is limited, and that both JAAM-DIC score and ISTH overt-DIC score can be used in septic shock patients. Trial registration clinicaltrial; Trial registration number: NCT02391792; Date of registration: 18/03/2015; URL of trial registry record: https://clinicaltrials.gov/ct2/show/NCT02391792?term=meziani&draw=4&rank=1